Ochrona konsumenta usług bankowych - Swat, Bogumiła (Consumer Protection in the Banking Services, 2005)
The article describes the progress in the Polish law and institution standards related to consumer protection in the banking services. The author analyses decision making in the clearing, deposits and loan process which protect bank consumers rights.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 151-166